The Moderating Effect of its Working Capital Management Policy on the Relationship between Dividend Policy and Stock Price: A Case Study on the Manufacturing Sector on the Kuwait Stock Exchange for the years 2019-2023 - Hassan, Barham; Sangawi, Shakhawan; Ahmed, Hadi (Journal of Economics and Administrative Sciences, 2025)
This study aims to examine the moderating effect of working capital management policies on the relationship between dividend policy and stock prices in the manufacturing sector of the Kuwait Stock Exchange (KSE) from 2019 to 2023. Grounded in signaling theory and agency theory, the research investigates how dividend decisions affect market valuation and how investment and financing strategies, particularly aggressive or conservative working capital approaches, influence this relationship. To achieve this, panel data from 21 manufacturing firms listed on the KSE were analyzed using panel regression techniques method in EViews software. The market price per share (MPS) was used as the dependent variable, while earnings per share (EPS) and dividend per share (DPS) were the independent variables. Return on assets (ROA) was incorporated as a moderating variable. Profit after tax (PAT) and return on equity (ROE) were excluded due to statistical insignificance. The results indicate that the working capital management policies—specifically aggressive investment and financing strategies—as well as ROA significantly moderate the relationship between dividend policy and stock price. While hypotheses H2, H3, and H4 were supported, hypothesis H1, which posits a direct relationship between dividend policy and stock price, was not supported (p-value = 0.0619), indicating a weak negative correlation. These findings offer practical insights for financial managers, investors, and policymakers in emerging markets, highlighting the strategic importance of aligning dividend decisions with working capital policies to enhance stock performance.